ANALISIS AKUNTANSI PERSEDIAAN PERUSAHAAN MANUFAKTUR MENURUT PSAK NO 14 PADA PT AGUNG BUMI AGRO - Mei, Laras; Kustiningsih, Nanik; Firdaus, Rizalnur (Fakultas Ekonomi Universitas Wisnuwardhana, 2021)
Abstract Inventory is one of the important things for a company, this isbecause most of the assets owned by the company are located on theinventory account side. For trading and manufacturing companies,inventory can be said to be the life or heart of the business, because thecompany's main business activity comes from the availability of inventorystocks. Therefore, the application of inventory accounting inmanufacturing companies is necessary to avoid the occurrence of OverStock (OS) or Out Of Stock (OOS). The purpose of research at PT AgungBumi Agro is to find out whether the application of PT Agung Bumi Agro'sinventory accounting is in accordance with PSAK No. 14 Revised of 2015.This research was conducted by comparing the process of implementingPT Agung Bumi Agro's inventory accounting with the applicableprovisions of PSAK No. 14 Revision of 2015. The results obtained in thisstudy explain that the inventory accounting income at PT Agung BumiAgro is good in terms of inventory definition, inventory measurement,recognition as expense and disclosure of inventories have beenimplemented in accordance with PSAK No. 14, 2015 Revision.Keywords : Inventory; PSAK No 14, 2015 Revision; InventoryValuation; Inventory Recording